In situ autophagy regulation in synergy with phototherapy for breast cancer treatment - Huijuan Zhang; Xiangyang Xuan; Yaping Wang; Zijun Qi; Kexuan Cao; Yingmei Tian; Chaoqun Wang; Junbiao Chang; Zhenzhong Zhang; Lin Hou (Elsevier, 2024)
Autophagy is an important factor in reducing the efficacy of tumor phototherapy (including PTT and PDT). Accurate regulation of autophagy in tumor cells is a new strategy to improve the anti-tumor efficiency of PTT/PDT. This project intended to construct a tumor-activated autophagy regulator to efficiently block PTT/PDT-induced autophagy and realize synergistic sensitization to tumor phototherapy. To achieve this goal, we first synthesized TRANSFERRIN (Tf) biomimetic mineralized nano-tellurium (Tf-Te) as photosensitizer and then used disulfide bond reconstruction technology to induce Tf-Te self-assembly. The autophagy inhibitor hydroxychloroquine (HCQ) and iron ions carried by Tf were simultaneously loaded to prepare a tumor-responsive drug reservoir Tf-Te/HCQ. After entering breast cancer cells through the "self-guidance system", Tf-Te/HCQ can generate hyperpyrexia and ROS under NIR laser irradiation, to efficiently induce PTT/PDT effect. Meanwhile, the disulfide bond broke down in response to GSH, and the nanoparticles disintegrated to release Fe2+ and HCQ at fixed points. They simultaneously induce lysosomal alkalinization and increased osmotic pressure, effectively inhibit autophagy, and synergistically enhance the therapeutic effect of phototherapy. In vivo anti-tumor results have proved that the tumor inhibition rate of Tf-Te/HCQ can be as high as 88.6% on 4T1 tumor-bearing mice. This multifunctional drug delivery system might provide a new alternative for more precise and effective tumor phototherapy.